Asset Pricing on London Stock Exchange in The Conventional And Downside Risk Approach - Anna Rutkowska-Ziarko; Leslaw Markowski; Chris Pyke (Communications of International Proceedings, 2021)
The aim of the study is to verify the pricing of assets on the London Stock Exchange using CAPM and D-CAPM. In this study the risk-return relationships were estimated using realised returns in cross-sectional regressions. In CAPM relations the risk was considered in a classical and downside risk framework. For calculating the downside risk the three formulas from Bawa and Lindenberg (1977), Harlow and Rao (1989) and Estrada (2002) for downside risk. The subject of the research were stocks from the FTSE 100 index and equally-weighted portfolios based on these stocks. The cross-sectional models give  evidence of an existing risk premium associated with Sharpe beta and downside beta confirming both CAPM and D-CAPM. The downside risk premiums were significantly higher than the Sharpe beta premiums except for the results obtained with the Bawa-Lindenberg beta coefficient.
Keywords: CAPM; Downside beta; LPM; semi-variance